2020
DOI: 10.1183/13993003.01398-2020
|View full text |Cite
|
Sign up to set email alerts
|

Active tuberculosis, sequelae and COVID-19 co-infection: first cohort of 49 cases

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disease (COVID-19) pandemic has attracted interest because of its global rapid spread, clinical severity, high mortality rate and capacity to overwhelm healthcare systems [1, 2]. SARS-CoV-2 transmission occurs mainly through droplets, although surface contamination contributes and debate continues on aerosol transmission [3-5]. The disease is usually characterised by initial signs and symptoms [4-9] similar to those of related viral infections (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
424
3
47

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(486 citation statements)
references
References 15 publications
12
424
3
47
Order By: Relevance
“…One had worsening chest radiographs and the other had improved imaging findings when compared to their last pre-COVID-19 studies; both survived [14]. A three-month-old Gambian child with COVID-19 was diagnosed with pulmonary and extrapulmonary tuberculosis (including meningitis) 3 days later and was placed on anti-tuberculous medications, but no details of how the diagnosis was reached were provided [16]. Further investigation into the role of co-infection by Mycobacterium tuberculosis and SARS-CoV-2 on severity and mortality is needed for both adults and children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One had worsening chest radiographs and the other had improved imaging findings when compared to their last pre-COVID-19 studies; both survived [14]. A three-month-old Gambian child with COVID-19 was diagnosed with pulmonary and extrapulmonary tuberculosis (including meningitis) 3 days later and was placed on anti-tuberculous medications, but no details of how the diagnosis was reached were provided [16]. Further investigation into the role of co-infection by Mycobacterium tuberculosis and SARS-CoV-2 on severity and mortality is needed for both adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…Demonstration of SARS-CoV-2 RNA in the central nervous system (CNS) has only been documented in three adults, one with a positive CSF RNA result, one using genome sequencing in CSF, and another utilizing transmission electron microscopy on brain tissue obtained post-mortem [5,8,9]. Pulmonary co-infections with common viral, bacterial, and fungal pathogens have been described in COVID-19 patients, but there is a paucity of literature on mycobacteria, including members of the Mycobacterium tuberculosis complex with which a third of the world population is infected [10][11][12][13][14][15][16][17]. We describe the unique case of a previously healthy child with acute SARS-CoV-2 infection, fever, and headache, with laboratory and imaging evidence of meningoencephalitis who rapidly deteriorated 2 weeks into her illness and was found to have both SARS-CoV-2 RNA and Mycobacterium tuberculosis complex DNA on a cerebellar biopsy with histopathology consistent with tuberculous meningitis, with the recovery of Mycobacterium tuberculosis from two tracheal aspirates several weeks after she died.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship could not be underestimated as few studies have recently reported coinfection of SARS-CoV-2 with TB as summarized in Table 1. [12][13][14][15][16][17][18][19] An observational study recently reported that persons with latent TB have increased susceptibility for SARS-CoV-2 infection associated with rapid progression and severe involvement. [16] TB infection was more common among patients with SARS-CoV-2 infection than in those with bacterial or other viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Vermutlich ist nach einer erfolgreich behandelten TB ohne resultierende Folgeschäden weder die Wahrscheinlichkeit erhöht, eine SARS-CoV-2-Infektion zu bekommen, noch einen schweren Verlauf zu entwickeln. Komorbiditäten und Alter sind allerdings auch in diesem Zusammenhang entscheidende Einflussfaktoren [8].…”
unclassified
“…Für eine heterogene internationale Kohorte (SARS-CoV-2 + Tuberkuloseerkrankung n = 42; SARS-CoV-2 + Folgeschäden nach überstandener Tuberkulose n = 7) wurde eine Case Fatality Rate von 12,3 % beschrieben, wobei 5 der 6 Verstorbenen älter als 60 Jahre waren und an mindestens einer Begleiterkrankung litten. Die Autoren können aus den bislang vorliegenden Daten keinen kausalen Zusammenhang zwischen Tuberkuloseerkrankung und Mortalität ableiten [8]. Eine Kann ich mich mithilfe einer Tuberkulose-Impfung (Bacille Calmette-Guérin; BCG) vor einer Infektion mit SARS-CoV-2 schützen?…”
unclassified